Connecting Theoretical Perspectives and Praxis on African Women Leadership and Development Agenda - Costa, King; Ngcetane-Vika, Thelela (My University, 2021)
African women are becoming increasingly relevant in the continent's development and growth agenda. For decades, African women have been seen as a backbone and connective tissue for spiritual growth and sustainable societies, in fields such as religion, culture, economics, and politics, to name a few. This review is part of PhD studies on African women leadership development. The aim of this paper is to explore a functional connection between theoretical perspectives and practical application in real life regarding the agenda on developing leadership capabilities for women. A qualitative evidence synthesis was used as a method of inquiry and thematic expressions were developed using the COSTA QDA Technique. Results culminated in three thematic expressions that explicated a disconnect between popular theories on women development agenda and practical application in a collaborative approach. However, an emphasis was made on the requirement for women in influential leadership positions to coach and mentor others. Findings further indicated that women at grassroots level were enthusiastic and ready for programmes and environments that enable leadership capabilities, development and growth. The study concluded that formal and sustainable mentorship and coaching programmes that integrate all stakeholders (males and females) in a collaborative approach should be developed.
Keywords: African women; Leadership capabilities; Leadership development